2022
DOI: 10.3389/fpsyt.2022.843254
|View full text |Cite
|
Sign up to set email alerts
|

Alternations in Dynamic and Static Functional Connectivity Density in Chronic Smokers

Abstract: Previous studies have implicated abnormal functional coordination in brain regions of smokers. Neuroimaging studies demonstrated alternations in brain connectivity by using the resting-state functional connectivity (rsFC) method which arbitrarily chooses specific networks or seed regions as priori selections and cannot provide a full picture of the FC changes in chronic smokers. The aim of this study was to investigate the whole-brain functional coordination measured by functional connectivity density (FCD). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…LG is involved in the processing of visual memory, especially in the processing of words. Integrating visual information is believed to be a crucial function of the cuneus ( Yang et al, 2022 ). Numerous investigations ( Pang et al, 2021 ; Wills et al, 2021 ) have revealed that mTLE patients have functionally impaired occipital cortex.…”
Section: Discussionmentioning
confidence: 99%
“…LG is involved in the processing of visual memory, especially in the processing of words. Integrating visual information is believed to be a crucial function of the cuneus ( Yang et al, 2022 ). Numerous investigations ( Pang et al, 2021 ; Wills et al, 2021 ) have revealed that mTLE patients have functionally impaired occipital cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the parameter settings in previous studies, we used different window lengths (i.e., 30 TRs [60 s], 80 TRs [160 s]) and step sizes (i.e., 3 TRs [6 s] and 5 TRs [10 s]) to exclude the influence of parameter selection and to verify dFC stability [ 29 – 32 ]. Meanwhile, the static FC map of each ROI was calculated and compared voxel-wise between OCD and HCs.…”
Section: Methodsmentioning
confidence: 99%
“…Such transition has been suggested that associated with a functional shift in subregions of striatum: Exaggerated responses of the ventral striatal reward system engaged in excessive substance using at an early stage, while dorsal part dominated after the formation of compulsive behaviours 9,10 . Although the VTA and striatum played an important role in describing the reaction‐related features of tobacco addiction, results from recent neuroimaging studies have implicated the additional brain regions, especially the prefrontal cortex (PFC) 10,11 . Goldstein's study found that PFC is involved in regulating cognitive and emotion process, which could result in the overvaluing of drug reinforcers, the undervaluing of alternative reinforcers, and impaired inhibitory control for substance response 12 .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Although the VTA and striatum played an important role in describing the reaction-related features of tobacco addiction, results from recent neuroimaging studies have implicated the additional brain regions, especially the prefrontal cortex (PFC). 10,11 Goldstein's study found that PFC is involved in regulating cognitive and emotion process, which could result in the overvaluing of drug reinforcers, the undervaluing of alternative reinforcers, and impaired inhibitory control for substance response. 12 Such changes in addiction were described as a model called impaired response inhibition and salience attribution (I-RISA).…”
Section: Introductionmentioning
confidence: 99%